1974
DOI: 10.1159/000193095
|View full text |Cite
|
Sign up to set email alerts
|

Blutgaswerte und Atemwegswiderstand bei Gesunden und Patienten mit obstruktiven Atemwegserkrankungen vor und nach Höhenadaptation

Abstract: In 49 patients with obstructive airways disease and 15 normal subjects O2 and CO2 tension in arterial blood, vital capacity, maximal midexpiratory flow rate and forced expiratory volume were studied at 524, 1,600, and 2,844 m altitude. There was an acute decrease in O2 and CO2 tension and an increase of maximal midexpiratory flow rate. After an adaptation period of 10-12 days to 1,600 m in 70% of the patients an increase of the O2 tension and a decrease of the airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Overall, 56 original articles reporting data on ABGs under hypobaric hypoxic conditions among healthy volunteers met inclusion criteria. A Galbraith plot including those 56 studies identified 3 visual outliers, which were excluded (eResults and eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 56 original articles reporting data on ABGs under hypobaric hypoxic conditions among healthy volunteers met inclusion criteria. A Galbraith plot including those 56 studies identified 3 visual outliers, which were excluded (eResults and eFigure 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 53 studies reporting 115 group ascents to altitudes between 1524 m and 8730 m were included in the aggregated data analysis. Two of those studies (3.8%) were not incorporated into the forest plot due to missing measurements of variance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations